Impact of Extra-Eu Exports on Economic Non-European Countries’ Growth: Panel Evidence from 140 Partners - Dong, Luyan; Fabus, Michal; Tvaronaviciene, Manuela (Transformations In Business & Economics, 2026)
This study examines the impact of extra-EU exports on the GDP of trading partners, with a particular focus on the moderating role of export trade efficiency. Using panel data from 140 partners over 22 years (2000–2021), pooled OLS, random effects, fixed effects, and correlated random effects models are employed to assess both short and long-term impact of extra-EU exports on economic growth. Regression analysis reveals a statistically significant positive correlation between extra-EU exports and the GDP of partner countries, demonstrating a dual transmission mechanism: short-term demand-side stimulation through fluctuations in export volume and long-term supply-side structural impacts through the optimisation of export composition and adjustments to trade policy. Further research indicates that the moderating effects of trade efficiency primarily stem from long-term factors, such as the deepening of free trade agreements, the implementation of trade facilitation measures, and improvements in market openness. The study provides critical insights for policymakers and economists, particularly in the new era of trade tensions, where extra-EU exports play a vital role in sustaining global economic recovery.